Validation of the use of short message service (SMS) as a training tool for anaesthetic nurses - Duys, Rowan Alexander (Department of Anaesthesia, 2015)
Background: Anaesthetic nurses form a critical part of the team providing peri-operative care to patients, but no accredited training exists for them in South Africa. In this setting, without a formal training programme, short in-service training interventions are a pragmatic attempt at improving nurse performance and patient outcomes. Traditional didactic teaching formats have limitations, and mLearning (the use of mobile telephones to facilitate education) has proven equivalent or superior to traditional teaching methods in several settings. Despite very high levels of mobile phone ownership amongst healthcare workers in Africa, this form of educational delivery has not been tested in the hospital-based nursing population. Methods: A telephonic True/False Pre-Test was performed with 12 nurses of varying levels of training, to assess their pre-existing knowledge of anaesthesia. A pre-learning package was then delivered to them in the form of daily SMS’s for a month covering relevant anaesthesia content. A telephonic post-intervention test was performed to assess if anaesthesia theory knowledge had improved. Results: Median test scores were compared using a Wilcoxon Signed Rank test and were statistically higher in the post-intervention test: 83,3% (IQR 66,7-86,7) vs. 70% (IQR 66,7-71,7) (p=0,018). Conclusions: The results show that knowledge scores of hospital-based anaesthetic nurses can be improved using training by SMS, thus validating the use of the mobile phone as a cheap, widely accessible and effective educational vehicle.